How do diverse low-income and middle-income countries implement primary healthcare team integration to support the delivery of comprehensive primary health care? A mixed-methods study protocol from India, Mexico and Uganda - David Peiris; Felicity Goodyear-Smith; Rohina Joshi; Leticia Ávila-Burgos; Manushi Sharma; Edson Serván-Mori; Robert James Mash; Innocent Besigye; Emanuel Orozco-Nuñez; D Praveen; Ileana Heredia-Pi; Hortensia Reyes-Morales; et al. (BMJ Open, 2022)
Introduction Attainment of universal health coverage is feasible via strengthened primary health systems that are comprehensive, accessible, people-centred, continuous and coordinated. Having an adequately trained, motivated and equipped primary healthcare workforce is central to the provision of comprehensive primary healthcare (CPHC). This study aims to understand PHC team integration, composition and organisation in the delivery of CPHC in India, Mexico and Uganda.Methods and analysis A parallel, mixed-methods study (integration of quantitative and qualitative results) will be conducted to gain an understanding of PHC teams. Methods include: (1) Policy review on PHC team composition, organisation and expected comprehensiveness of PHC services, (2) PHC facility review using the WHO Service Availability and Readiness Assessment, and (3) PHC key informant interviews. Data will be collected from 20, 10 and 10 PHCs in India, Mexico and Uganda, respectively, and analysed using descriptive methods and thematic analysis approach. Outcomes will include an in-depth understanding of the health policies for PHC as well as understanding PHC team composition, organisation and the delivery of comprehensive PHC.Ethics and dissemination Approvals have been sought from the Institutional Ethics Committee of The George Institute for Global Health, India for the Indian sites, School of Medicine Research Ethics Committee at Makerere University for the sites in Uganda and the Research, Ethics and Biosecurity Committees of the Mexican National Institute of Public Health for the sites in Mexico. Results will be shared through presentations with governments, publications in peer-reviewed journals and presentations at conferences.